Activity-based cost analysis of hepatic tumor ablation using CT-guided high-dose rate brachytherapy or CT-guided radiofrequency ablation in hepatocellular carcinoma. Issue 1 (December 2016) - Schnapauff, D.; Collettini, F.; Steffen, I.; Wieners, G.; Hamm, B.; Gebauer, B.; Maurer, M.
Abstract Purpose To analyse and compare the costs of hepatic tumor ablation with computed tomography (CT)-guided high-dose rate brachytherapy (CT-HDRBT) and CT-guided radiofrequency ablation (CT-RFA) as two alternative minimally invasive treatment options of hepatocellular carcinoma (HCC). Materials and methods An activity based process model was created determining working steps and required staff of CT-RFA and CT-HDRBT. Prorated costs of equipment use (purchase, depreciation, and maintenance), costs of staff, and expenditure for disposables were identified in a sample of 20 patients (10 treated by CT-RFA and 10 by CT-HDRBT) and compared. A sensitivity and break even analysis was performed to analyse the dependence of costs on the number of patients treated annually with both methods. Results Costs of CT-RFA were nearly stable with mean overall costs of approximately 1909 €, 1847 €, 1816 € and 1801 € per patient when treating 25, 50, 100 or 200 patients annually, as the main factor influencing the costs of this procedure was the single-use RFA probe. Mean costs of CT-HDRBT decreased significantly per patient ablation with a rising number of patients treated annually, with prorated costs of 3442 €, 1962 €, 1222 € and 852 € when treating 25, 50, 100 or 200 patients, due to low costs of single-use disposables compared to high annual fix-costs which proportionally decreased per patient with a higher number of patients treated annually. A break-even between both methods was reached when treating at least 55 patients annually. Conclusion Although CT-HDRBT is a more complex procedure with more staff involved, it can be performed at lower costs per patient from the perspective of the medical provider when treating more than 55 patients compared to CT-RFA, mainly due to lower costs for disposables and a decreasing percentage of fixed costs with an increasing number of treatments.